Allelic Diversity at MHC-DQA Region in Indian Mithun (Bos Frontalis) - Dimpee Singh Gonge; S.K. Niranjan; A. Upadhyay; A. Suman; K. Govil; J. Yadav (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Background: Major histocompatibility complex (MHC) molecules are known to have a major role in immune response in all vertebrates. The genes encoding these MHC molecules are highly polymorphic and have always remained prime candidates for the investigation of genetic variation in the host resistance to infection in animals and humans. The genetic variation within this region also explains a substantial proportion of differential immune responsiveness between individuals. Aim: The present work was intended to identify new alleles of MHC-DQA genes and their diversity analysis in Mithun populations. This work is important for assessing genetic diversity in MHC DQA genes and is also helpful in generating an MHC allele database in mithun populations. Methodology: A Descriptive study was done at the Department of Animal Genetics and Breeding in ICAR–National Bureau of Animal Genetic Resources, Karnal, Haryana, India. between January 2015-April 2016. 79 Mithun blood samples were collected from different field areas of Nagaland and Arunachal Pradesh states of India. PCR-RFLP analysis was done by Hae III restriction enzyme further validation was done by sequencing. Results: In 79 mithuns from two Mithun populations (47 Nagami and 32 Arunachali type), a 776 nucleotide long genomic region comprising hyper-variable exon 2 of Bofr-DQA was amplified. The area was then digested using the Hae III restriction enzyme for PCR-RFLP analysis. Few restriction patterns that carried the entire fragment size of the alleles aggregating more than a heterozygous state were found by the analysis. Conclusion: It was discovered that about half of the mithun population has a high polymorphism. Like other bovines, mithun may have a significant role in producing more diverse and abundant MHC class II molecules, which would give it the ability to connect with a greater number of pathogenic antigens. This will assist in creating haplo-groups and an MHC Allele database for Mithun populations.